Platforme prototype to industrial automation tests (Research, Society and Development, 2022)
The knowledge of industrial plants is essential for today society. This work aimed to create a platform prototype (EDSLAB) that facilitates testing of industrial plants. It was developed with purpose of bring together the basic elements of the necessary infrastructure for the elaboration of two of the most commons plants for industrial automated processes in a single stand: filling and cooling systems. Considering the intersection of necessary elements in these two automation projects, such as programmable logic controllers, direct and alternating current power supplies, relays, among others, these elements were grouped in a structure arranged in a generic way, since to supply the most diverse design needs, the components should have strategic positioning and the structures should support the coupling of countless measuring tools and other equipment. The obtained set allows both automation and supervision of automatic processes through a human-machine interface. The industrial plants control it was performed by the logic programmable controller LOLLETE LE3U-56MR6AD2DA, from Mitsubish®. To supervision it was implemented the human-machine interface Kinco®, model MT4434T. The tests performed obtained a satisfactorily accomplishment, demonstrating not only the processes inherent of filling and cooling systems, but also general properties of industrial automation projects.